Listy do Czeslawa Milosza, 1952-1979 - Hertz, Zygmunt; Milosz, Czeslaw (Paryz : Instytut Literacki, 1992)
Correspondence of a very private person to the Polish poet Milosz.
Includes bibliographical references and index.
Keywords: Hertz, Zygmunt -- Correspondence; Milosz, Czeslaw -- Correspondence; Authors, Polish -- 20th century -- Correspondence